Порівняльний аналіз трав’яних біотопів України за показниками багатства та різноманітності - Kuzemko, A. A. (Національний дендрологічний парк "Софіївка" НАН України, 2021)
Using the big dataset (17,687 vegetation plots), a comparative analysis of grassland habitats of Ukraine in terms of species richness, Shannon and Simpson diversity indices and Pielou and Smith-Wilson evenness indices was performed. Leading positions of thermophilous forest fringe and hay meadows, especially mountain ones, in almost all indices were revealed. Instead, halophytic habitats show the lowest rates in the vast majority of analyzes. In addition to these general patterns, the analysis revealed the following trends: in almost all analyzes (except for the values of the Smith- Wilson index) habitats formed on carbonate rocks had greater richness and diversity than those formed on rocks of silicates; in almost all cases (except the Pielou index) oligotrophic wet grasslands were characterized by higher values of richness and diversity than eutrophic ones; in all analyzes, mountain habitats were characterized by higher values of richness and diversity than similar lowland habitats.